A case of von Hippel-Lindau disease with multi-organ involvement: a rare case report - Bhuyan, Mrinal; Saha, Debadatta; Baishya, Basanta Kumar; Ghanghoria, Ashish (International Surgery Journal, 2020)
Von Hippel-Lindau (VHL) disease is a rare autosomal dominant syndrome manifested by a spectrum of tumours in the central nervous system (CNS) and other visceral organs. We herein report a case of 35 years aged newly diagnosed diabetic female patient presented with headache, gait instability, loss of vision in both eyes, left sided hearing impairment and subsequently diagnosed to have VHL disease. The pathophysiology involves the inactivation of the VHL tumour suppressor gene. Early recognition and treatment remains the mainstay of management. Even many years after the complete tumour excision, newer neoplasms may develop. Increasing knowledge about the molecular enabled us to investigate the role of anti-angiogenic drugs. Continuous surveillance at regular interval must be conducted in patients with VHL disease.